A teacher's citizenship as status and practice in the first half of the twentieth century. Issue 3 (1st September 2017) - Whitehead, Kay
This article explores the citizenship practice of an Australian kindergarten teacher, Marjorie Caw (nee Hubbe) who was born in 1893, a few months prior to the achievement of women's suffrage in South Australia. First, the Hubbe family is located politically and socially in the Australian context. Then the article positions Marjorie as a young citizen teacher at the Adelaide Kindergarten Training College and Grey Ward Free Kindergarten between 1911 and 1913. The next section focuses on the implications of her German surname during the First World War and exposes the precarious nature of citizenship status. Marjorie married in 1922 and the final section analyses citizen mother Marjorie's understanding of active citizenship in the diverse rural community of Kojonup, Western Australia. The article argues that citizenship is not only a legal concept but also involves complex political, social and affective relationships which change over time and in different contexts. Marjorie's citizenship practice was a classed, raced and gendered process of inclusion and exclusion in the first half of the twentieth century.